INTERPRETATION OF CONCEPTUAL METAPHORS IN ENVIRONMENTAL MEDIA TEXTS - To‘rayeva , Maftuna Ravshanovna; Yugay , Yevgeniya Viktorovna (Innovative Development in Educational Activities, 2024)
This article delves into the analysis of conceptual metaphors in environmental media texts, exploring how language is used to convey complex ideas and emotions related to the environment. By examining the use of metaphors in environmental discourse, we aim to understand how these linguistic tools shape our perceptions of nature, sustainability, and climate change.